CUSTOMER PREFERENCE AND SATISFACTION: A COMPARATIVE STUDY BETWEEN SRI LANKA INSURANCE COMPANY AND CEYLINCO INSURANCE COMPANY IN VAVUNIYA DISTRICT - Inthuza, S.; Pushpanathan, A. (University of Colombo, 2012)
The insurance industry provides protection against financial losses resulting from a variety of hazards. There are various insurance companies provide its service to peoples in Vavuniya District. The present study is to analysis the customer preference and satisfaction of Sri Lanka Insurance Company and Ceylinco Insurance Company. Research question of this study is “what is the level of customer preference and satisfaction of the service of Sri Lanka Insurance and Ceylinco Insurance Company?” The objectives of this study are to determine the level of customer satisfaction and preference of the insurance services of Sri Lanka Insurance and Ceylinco Insurance, to examine about the customer relationship management, and to compare customer preference between the insurance industries. 100 customers (50 Sri Lanka Insurance & 50 Ceylinco Insurance customers) are selected from Vavuniya District by using random sampling method. Data gathered from the respondents through the questionnaire (5 Likert scale) and interview. Data were entered in to the SPSS 16.0 package. The correlation and regression analysis were done in this study. The finding of this study is indicated that the customer preference was a high level with the overall marketing mix of Sri Lanka Insurance than Ceylinco Insurance (Sri Lanka Insurance r=0.665 p<0.01, Ceylinco Insurance r=0.346, p<0.05).These overall findings show that most of the Sri Lanka Insurance customers dissatisfied with the poor knowledge of policies, inconvenient place, higher charges for vehicle and other general insurance and their investment are very difficult to return. However Ceylinco Insurance Company has more satisfied these overall analyses the customer satisfy with Ceylinco Insurance service providers than Sri Lanka Insurance service providers. This satisfaction leads to preference. Customer satisfied both companies’ services. But there are lots of competitions in this insurance industry. So these companies have to introduce the variety of services and increasing the quality and available supply.
Keywords: Customer; Satisfaction; Preferences; Marketing Mix; Insurance Companies